Empowerment of social forestry business group in improving village welfare in South Lampung - Aam Amaliyah; Saifuddin Saifuddin; Tontowi Jauhari (Community Empowerment, 2023)
The social forestry program is one of the government's instruments that aims to improve the welfare of communities around forest areas without destroying forests. In order to improve the welfare of the people living around the forest area, it is necessary to develop a social forestry business through the Kelompok Usaha Perhutanan Sosial (KUPS) which is determined by the Head of the Forest Management Unit (KPH). One of the villages with a social forestry program is Way Kalam Village, Penengahan District, South Lampung Regency, where 90% of the community depends on plantations and agriculture around the forest area and consists of 6 KUPS based on the commodities produced. The method used is awareness, knowledge, understanding, utilization, and use of skills. The activity results from the empowerment have not impacted material welfare due to several obstacles including the capital, marketing, and institutional issues that are more dominant. However, the existence of empowerment has an impact on immaterial welfare where people can participate and have great opportunities so they can develop their potential and their business.